Interference Analysis Between 5G System and Fixed Satellite Service in the 28 GHz Band - Ghifari, Rafli; Sari, Lydia; Mardian W, R. Deiny; Alam, Syah; Surjati, Indra (ELKHA : Jurnal Teknik Elektro, 2023)
One of the most favorable frequency bands for 5G technology is the 27.5 - 28.5 GHz band which has been used by Fixed Satellite System (FSS) service in the uplink direction. This potentially causes interference between the two systems. This study aims to analyze the interference that occurs between satellite earth stations and 5G access points (AP), and between 5G AP and satellite sky stations. The analysis is carried out based on simulations using the Spectrum Engineering Advanced Monte Carlo Analysis Tool (SEAMCAT) software, with two scenarios. The first scenario is to analyze interference between the 5G AP and the FSS sky station. With the C/I interference criterion of 40.2 dB, the simulation results show that the 5G AP will not interfere with the FSS sky station. The second scenario is the interference simulation between FSS earth station and 5G AP. The simulation is carried out by varying the distance between the earth station and the 5G AP, the height of the earth station, and the height of the 5G AP. Based on the simulations, it is shown that the FSS earth station can interfere with 5G AP with a probability of up to 60%, so it is necessary to adjust the distance between systems and the height of the antenna to minimize the interference. The shortest distance needed to minimize interference is 36 km with an earth station height of 5 meters.